(untitled) (Web of Teachers: Inderscience Research, 2025)
The establishment of the principles of psycholinguistics laid the foundation for cognitive linguistics. The existence of non-verbal thinking and the constantly changing and updating conceptual sphere, which includes concepts in people’s minds, was substantiated by psycholinguists. According to the study, people create signs to exchange important data of common and popular concepts, although in the space of conceptual meanings, language signs are like a dotted line, and the conceptual sphere is much larger than language tools, which are only a part of it.